Pengakuan Akuntansi Hibah Pemerintah Terhadap Laporan Keuangan PT Bank Pembangunan Daerah Lampung Tahun 2020 - Nadira Zahra Alifia; Nailah Artanti; Ni Made Dinda Savitri Utami; Riska Aulia Salsabila Fadhly (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
PSAK 61 is an accounting standard that explains the accounting for government grants and disclosure of government assistance. This study aims to determine the accounting recognition of grants contained in the financial statements of PT Bank Pembangunan Daerah Lampung. The object used in this research is PT Bank Pembangunan Daerah Lampung. This research is an exploratory research with a wider scope of research. The type of data in this study is descriptive or in the form of a description. This study uses secondary data sources with descriptive analysis method. The results of this study explain that government grants received by PT Bank Lampung have been prepared in accordance with the provisions in PSAK 61 through the income method.